Citing Others' Works in Academic Texts: How Non-native Writers of English Across-disciplines Use Reporting Verbs and Reporting Signals in Their Research Article Introductions - Safnil Arsyad; Syahrial Syahrial; Husnul Hakim (Masyarakat Linguistik Indonesia Universitas Andalas, 2021)
This study is aimed at investigating how Indonesian writers in multidiscipline use reporting verbs (henceforth RVs) and reporting signals (henceforth RSs) in their research article introductions in English. Fifty research articles (henceforth RAs) were chosen on purpose from the recent edition of five different English language journals in Multi-disciplines published in Indonesia (i.e., 10 from Applied Linguistics, 10 from Medicine, 10 from Animal Husbandry, 10 from Engineering and Technology, and 10 from Geography). The results reveal that the most frequent groups of RV found in the RA introductions are SHOW and ARGUE groups; while the most frequent RS is Reporting Noun. It is also found that Indonesian writers in the data of this research tend to use RVs in Present and Past Tense. These findings are similar to those of previous studies where there is no important difference between English native and non-native speakers in using RVs in their RAs. This implies that Indonesian writers of the articles used in this study have used RVs in a similar way to English native speakers. This is because the RAs used in this research were taken from reputable international journals indexed by Scopus and/or Web of Science.